2012
DOI: 10.1371/journal.pone.0037792
|View full text |Cite
|
Sign up to set email alerts
|

Immune and Viral Correlates of “Secondary Viral Control” after Treatment Interruption in Chronically HIV-1 Infected Patients

Abstract: Upon interruption of antiretroviral therapy, HIV-infected patients usually show viral load rebound to pre-treatment levels. Four patients, hereafter referred to as secondary controllers (SC), were identified who initiated therapy during chronic infection and, after stopping treatment, could control virus replication at undetectable levels for more than six months. In the present study we set out to unravel possible viral and immune parameters or mechanisms of this phenomenon by comparing secondary controllers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 60 publications
2
55
0
Order By: Relevance
“…Antiretroviral therapy (ART) in HIV-1-infected individuals suppresses plasma HIV-1 RNA below limits of detection by standard clinical assays within 3-6 months. However, despite long-term ART, some infected cells continue to transcribe viral RNA as indicated by the presence of cellular HIV-1 transcripts and low-level viremia detected by ultrasensitive single-copy assay (SCA) [14][15][16][17]. The decay kinetics of viral transcriptional activity, measured as cell-associated unspliced HIV-1 RNA (CA-US HIV-1 RNA), in peripheral blood mononuclear cells (PBMCs) and lymphocytes residing in lymph nodes, follow roughly the same pattern as the decay kinetics of plasma HIV-1 RNA [18,19], although the reduction only occurs over 1-2 log 10 compared to the 3-6 log 10 reduction in plasma HIV-1 RNA [18].…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral therapy (ART) in HIV-1-infected individuals suppresses plasma HIV-1 RNA below limits of detection by standard clinical assays within 3-6 months. However, despite long-term ART, some infected cells continue to transcribe viral RNA as indicated by the presence of cellular HIV-1 transcripts and low-level viremia detected by ultrasensitive single-copy assay (SCA) [14][15][16][17]. The decay kinetics of viral transcriptional activity, measured as cell-associated unspliced HIV-1 RNA (CA-US HIV-1 RNA), in peripheral blood mononuclear cells (PBMCs) and lymphocytes residing in lymph nodes, follow roughly the same pattern as the decay kinetics of plasma HIV-1 RNA [18,19], although the reduction only occurs over 1-2 log 10 compared to the 3-6 log 10 reduction in plasma HIV-1 RNA [18].…”
Section: Introductionmentioning
confidence: 99%
“…The circumstances leading to a similar phenomenon among those started on ART during CHI are unclear. Immunologic studies of previously identified PTCs who started ART during CHI have reported low levels of HIV unspliced RNA in peripheral blood mononuclear cells compared to other ART-treated patients 20 . Further study of PTCs who started ART during CHI is needed to better delineate their underlying genetic, immunologic, and virologic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of PTCs is estimated at between 5% and 15% of patients beginning cART shortly after primary HIV infection [17][18][19][20], which is significantly higher than the proportion of HICs [21,22]. Such a significant proportion of PTCs has been observed only after early initiation of treatment and not when therapies were begun during the chronic phase, in which reported cases are even scarcer [23]. The rarity of PTCs worldwide may be explained by the fact that only a very small proportion (approx.…”
Section: Early Virus-host Interactions and Their Impact On Disease Prmentioning
confidence: 99%